New insights in presbyopia: impact of correction strategies - Amy L Sheppard; James S Wolffsohn; Leon N Davies (BMJ Open Ophthalmology, 2023)
Presbyopia occurs when the physiologically normal age-related reduction in the eyes focusing range reaches a point, when optimally corrected for distance vision, that the clarity of vision at near is insufficient to satisfy an individual’s requirements. Hence, it is more about the impact it has on an individual’s visual ability to function in their environment to maintain their lifestyle than a measured loss of focusing ability. Presbyopia has a significant impact on an individual’s quality of life and emotional state. While a range of amelioration strategies exist, they are often difficult to access in the developing world and prescribing is generally not optimal even in developed countries. This review identified the need for a standardised definition of presbyopia to be adopted. An appropriate battery of tests should be applied in evaluating presbyopic management options and the results of clinical trials should be published (even if unsuccessful) to accelerate the provision of better outcomes for presbyopes.